THE K4F MODEL FOR DEEP LEARNING POLICIES: INTEGRATIVE FRAMEWORK FOR ADAPTIVE GOVERNANCE AND POLICY LEARNING IN EDUCATION - Marina Dwi Mayangsari; Ahmad Suriansyah; Aslamiah; Sulistiyana (RADJA PUBLIKA, 2026)
The implementation of public policies often encounters many challenges due to a lack of coordination between sectors, a lack of technological access, and a limited policy learning process. This study used the Integrative Literature Review (ILR) approach. The aim of this study is to create a conceptual model of policy implementation by combining theoretical and empirical results from five reputable international journal articles discussing cross-sector public policies. This study was conducted in four systematic stages: (1) content analysis; (2) thematic mapping; (3) creating a conceptual model; and (4) contextual analysis of education policy issues related to deep learning in Indonesia. This study has novelty in integrative literature synthesis, resulting in the K4F (Key Four Factors Framework) model by comparing four main aspects, including leadership, collaboration, adaptive justice, and sustainable learning through framing elements as a binding element of values and policy direction. The K4F model showed that the success of a policy depends on the dynamic relationship between transformational leadership, collaboration, the social justice principle, and a sustainable policy learning system. This model not only broadens theoretical discourse regarding the understanding of adaptive governance and policy learning in education but also provides a practical contribution as a tool to assess the readiness and effectiveness of the implementation of policy in Indonesia related to learning using deep learning and artificial intelligence (AI) approaches.